2011
DOI: 10.1177/1069397111423898
|View full text |Cite
|
Sign up to set email alerts
|

Hofstede and Shane Revisited

Abstract: Hofstede’s value dimensions offer a measure of one component of culture (cultural values) and are a means of gaining greater understanding of the role culture plays in national innovation success. Hofstede’s (1980) cultural measures of individualism, uncertainty avoidance, and power distance, for example, have been shown to be correlated to the number (per capita) of trademarks (Shane, 1993). Via multivariate multiple linear regression, we assess the link between Hofstede’s measures of cultural values and inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 18 publications
1
58
1
Order By: Relevance
“…Our results are in accordance with the results of Waldman et al (2006), who showed that cultures with stronger power distance values may encourage managers to show very little concern for stakeholders such as employees, environmentalists and customers. In addition, power distance is strongly negatively associated to the level of innovation (Rinne, Steel, & Fairweather, 2012). Since one of the distinguishing characteristics of social entrepreneurship is innovation (Lepoutre et al, 2011), it may be argued that power distance influences social entrepreneurship through different channels, including both tolerance of social inequality level and innovation acceptance level.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in accordance with the results of Waldman et al (2006), who showed that cultures with stronger power distance values may encourage managers to show very little concern for stakeholders such as employees, environmentalists and customers. In addition, power distance is strongly negatively associated to the level of innovation (Rinne, Steel, & Fairweather, 2012). Since one of the distinguishing characteristics of social entrepreneurship is innovation (Lepoutre et al, 2011), it may be argued that power distance influences social entrepreneurship through different channels, including both tolerance of social inequality level and innovation acceptance level.…”
Section: Resultsmentioning
confidence: 99%
“…It concluded literally that uncertainty-accepting societies may be more innovative than uncertainty-avoiding societies, based on employees' preferences for different roles within their organizations. Intrigued by these findings, Rinne et al (2012) assessed the predictive properties of all of Hofstede's dimensions, using data from the complex Global Innovation Index as dependent variables. They found that while IDV-COLL and PD were related to national innovation scores, UA was not related to them.…”
Section: Variable R With Pdmentioning
confidence: 99%
“…However, with regard to this assumption, research has produced contradictory outcomes (Hofstede et al, 2010, pp. 211): Studies at national level have either found a negative relationship between uncertainty avoidance and innovation (Shane, 1993), or no relationship at all (Rinne et al, 2012). Hofstede et al (2010) argued that cultures with low uncertainty avoidance excelled at producing new ideas, while cultures with high uncertainty avoidance were better at implementing such ideas into new processes or products.…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%